Enhanced quality and quantity of retrieval of critically appraised topics using the CAT crawler. - Dong, P.
As healthcare moves towards the implementation of Evidence-Based Medicine (EBM), Critically Appraised Topics (CATs) become useful in helping physicians to make clinical decisions. A number of academic and healthcare organizations have set up web-based CAT libraries. The primary objective of the presented work is to provide a one-stop search and download site that allows access to multiple CAT libraries. A web-based application, namely the CAT Crawler, was developed to serve physicians with an adequate access to available appraised topics on the Internet. Important information is extracted automatically and regularlay from CAT websites, and consolidated by checking the uniqueness and availability. The principle of meta-search is incorporated into the implementation of the search engine, which finds relevant topics following keyword input. The retrieved result directs the physician to the original resource page. A full-text article of a particular topic can be converted into a proper format for downloading to Personal Digital Assistant (PDA) devices. In summary, the application provides physicians with a common interface to retrieve relevant CATs on particular clinical topics from multiple resources, and thus speeds up the decision making process.
Keywords: Evidence-Based Medicine; Critically Appraised Topics; Meta-search.; Internet; Information Retrieval; Personal Digital Assistant